Effect of decreased renal function on poor oncological outcome after radical cystectomy - Dongsu Kim; Wook Nam; Yoon Soo Kyung; Dalsan You; In Gab Jeong; Bumsik Hong; Jun Hyuk Hong; Hanjong Ahn; Bumjin Lim (Investigative and Clinical Urology, 2023)
Purpose: To evaluate the impact of preoperative renal impairment on the oncological outcomes of patients with urothelial carcinoma who underwent radical cystectomy. Materials and Methods: We retrospectively reviewed the medical records of patients with urothelial carcinoma who underwent radical cystectomy from 2004 to 2017. All patients who underwent preoperative 99mTc-diethylenetriaminepentaacetic acid renal scintigraphy (DTPA) were identified. We divided the patients into two groups according to their glomerular filtration rates (GFRs): GFR group 1, GFR≥90 mL/min/1.73 m2; GFR group 2, 60≤GFR<90 mL/min/1.73 m2. We included 89 patients in GFR group 1 and 246 patients in GFR group 2 and compared the clinicopathological characteristics and oncological outcomes between the two groups. Results: The mean time required for recurrence was 125.5±8.0 months in GFR group 1 and 85.7±7.4 months in GFR group 2 (p=0.030). The mean cancer-specific survival was 131.7±7.8 months in GFR group 1 and 95.5±6.9 months in GFR group 2 (p=0.051). The mean overall survival was 123.3±8.1 months in GFR group 1 and 79.5±6.6 months in GFR group 2 (p=0.004). Conclusions: Preoperative GFR values in the range of 60≤GFR<90 mL/min/1.73 m2 are independent prognostic factors for poor recurrence-free survival, cancer-specific survival, and overall survival in patients after radical cystectomy compared with GFR values of ≥90 mL/min/1.73 m2.